The Effects of Digital Taxation on E-Commerce and Online Business Models - Katyal, Ashu; Sinha, Dr. Sandhya; Kumari, Dr. Sweta; Samal, Dr. Ansuman; Rani , Dr. Jeya; Channappagoudra, Manjunath; Khurana, Sahil (International Journal of Accounting and Economics Studies, 2025)
E-commerce revolves around the buying and selling of goods through digital platforms, often called Commerce or E-Commerce, depending on where the traffic is coming from. One key element in online shopping is how engaged customers feel with the products and services on offer. The industry has invested heavily in understanding and leveraging “Internet Data Technologies” to enhance “Buyer Engagement,” all to boost lead conversion rates. Unfortunately, these rates often fall short, typically landing in the single digits. So, while there’s a steady influx of buyers visiting online commerce sites, their effectiveness still trails behind traditional retail, which usually enjoys conversion rates of about 6-7%, and can even hit 11% in certain areas. The bounce rate, which measures how engaging a platform is, tends to spike if a webpage takes longer than 3 seconds to load or requires more than 3 clicks to navigate. A website or app with a cumbersome user interface can easily deter potential buyers, leading to a higher bounce rate. Research from the Baymard Institute indicates that if a design forces users to create an account and share personal information right off the bat, it often backfires, causing many users to abandon their carts. By enhancing the user interface and overall experience, businesses could potentially reduce bounce rates by around 35%.